2014
DOI: 10.1155/2014/834815
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Phyllanthus niruri Leaves Displays In Vitro Antioxidant Activity and Prevents the Elevation of Oxidative Stress in the Kidney of Streptozotocin‐Induced Diabetic Male Rats

Abstract: P. niruri has been reported to possess antidiabetic and kidney protective effects. In the present study, the phytochemical constituents and in vitro antioxidant activity of P. niruri leaf aqueous extract were investigated together with its effect on oxidative stress and antioxidant enzymes levels in diabetic rat kidney. Results. Treatment of diabetic male rats with P. niruri leaf aqueous extract (200 and 400 mg/kg) for 28 consecutive days prevents the increase in the amount of lipid peroxidation (LPO) product,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 46 publications
5
24
0
1
Order By: Relevance
“…In this respect, our results were in accordance with previous studies [13,21]. Our finding that the levels of MDA were increased, accompanying the increase in renal lipid levels in the diabetes group, was in agreement with the results of a study showing that renal MDA levels are higher in STZ-induced diabetic male rats [22].…”
Section: Discussionsupporting
confidence: 93%
“…In this respect, our results were in accordance with previous studies [13,21]. Our finding that the levels of MDA were increased, accompanying the increase in renal lipid levels in the diabetes group, was in agreement with the results of a study showing that renal MDA levels are higher in STZ-induced diabetic male rats [22].…”
Section: Discussionsupporting
confidence: 93%
“…(25) This was in accordance with the current phytochemical screening results, which detected different phytochemical contents. Based on the total phenol content assay in this study, it was also revealed that P. niruri contained high phenol content and the highest total phenol content was obtained using rutin as equivalent, with the value of TPC was 424.29 µg RE/mg extract.…”
Section: Frap Activitysupporting
confidence: 91%
“…P. niruri is a wide-spread tropical plant, belonging to the Euphorbiaceae family, which has been widely used in Ayurvedic medicine for the treatment of bronchitis, anemia, leprosy and asthma [162]. Many studies have shown its antioxidant activity both in vitro and in vivo [163]. In fact, its high flavonoid and polyphenol content leads to ROS scavenging and chelating transition metal ion activities, which play pivotal roles in preventing the oxidation of low-density lipoproteins and in ameliorating the inflammatory condition.…”
Section: Plant-derived Metabolitesmentioning
confidence: 99%